Modulating delirium through stimulation (MoDeSt): study protocol for a randomized, double-blind, sham-controlled trial assessing the effect of postoperative transcranial electrical stimulation on delirium incidence - Sophie Leroy; Viktor Bublitz; Ulrike Grittner; Robert Fleischmann; Falk von Dincklage; Daria Antonenko (Trials)
Abstract Background Postoperative delirium (POD) is the most common neurological adverse event among elderly patients undergoing surgery. POD is associated with an increased risk for postoperative complications, long-term cognitive decline, an increase in morbidity and mortality as well as extended hospital stays. Delirium prevention and treatment options are currently limited. This study will evaluate the effect of transcranial electrical stimulation (tES) on the incidence of POD. Methods We will perform a randomized, double-blind, sham-controlled trial using single-session postoperative application of tES in the recovery room in 225 patients (> 65 years) undergoing elective major surgery. Patients will be randomly allocated (ratio 1:1:1) to one of three study groups: (1) alpha-tACS over posterior parietal cortex [2 mA, 20 min], (2) anodal tDCS over left dorsolateral prefrontal cortex [2 mA, 20 min], (3) sham [2 mA, 30 s]. Delirium will be screened twice daily with the 3-min diagnostic interview Confusion Assessment Method (3D-CAM) in the 5 days following surgery. The primary outcome is the incidence of POD defined as at least one positive screening during the five first postoperative days compared between tACS and sham groups. Secondary outcomes include delirium severity, duration, phenotype, postoperative pain, postoperative nausea and vomiting, electroencephalographic (EEG) markers, and fluid biomarkers. Discussion If effective, tES is a novel, easily applicable, non-invasive method to prevent the occurrence of POD. The comprehensive neurophysiological and biofluid assessments for markers of (neuro-)inflammation and neurodegeneration will shed light on the pathomechanisms behind POD and further elucidate the (after-)effects of tES. The potential implications for the postoperative recovery comprise enhanced patient safety, neurocognitive outcome, perioperative manageability but also reduced healthcare costs. Trial registration German Clinical Trial Registry DRKS00033703. Registered on February 23, 2024.